Enhancing encapsulation of filarial antigen Brugia malayi thioredoxin in nano-liposomes: The role of lecithin composition - Malathi Balasubramaniyan; Vimalraj Vinayagam; Moni Philip Jacob Kizhakedathil; Kaliraj Perumal (ADMET and DMPK, 2023)
Background and purpose: Lymphatic filariasis is a debilitating infectious disease prevalent in endemic areas, necessitating the development of an effective vaccine for eradication. Although recombinant vaccine candidates have been deemed safe, they often fail to provide sufficient protection, which can be overcome by encapsulating them in nano-liposomes. In this study, we have optimised the liposomal composition for enhanced stability and encapsulation of filarial antigen Brugia malayi thioredoxin (Bm-TRX). Experimental approach: Nano-liposomes were prepared using egg phosphatidylcholine (EPC) and cholesterol via thin-film hydration, followed by sonication and characterizing. Encapsulation efficiency was optimised using different weight ratios of EPC to cholesterol (8:2, 7:3, and 6:4) and total lipid (EPC+Cholesterol) concentration to antigen Bm-TRX (10:1, 10:2, and 10:3) followed by release kinetics study. Key results: Optimised parameters yielded spherical liposomes measuring 209 nm in diameter with narrow polydispersity. Our findings demonstrated the highest encapsulation efficiency of 70.685 % and stability of 10 hours for an EPC to cholesterol weight ratio of 7:3. The in silico study proved the antigenic nature of TRX. Conclusion: The liposomal formulations loaded with TRX, as optimized in this study, hold promise for improving antigen efficiency by enhancing stability, bioavailability, and prophylactic effects by acting as immune potentiators.